Clinico-anatomical elucidation of teres minor muscle - P, Deepika; Mehta, Vandana; R, Shobhit; F, Rizwana; KS, Rajesh (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Rotator cuff muscles (RCM) are the dynamic stabilisers of glenohumeral joint. Rotator cuff disorders are common and hence RCM have been the area of interest for researchers. Teres minor, a RCM, assists in lateral rotation at shoulder joint. Among all the RCM, anatomical variations in teres minor muscle have been least documented in literature and hence considered as a neglected muscle. The aim of the present study was to explore variant morphology, insertion sites and patterns of insertion of teres minor muscle. Sixty adult embalmed human cadavers were dissected to delineate the fibers of teres minor muscle, from their site of origin on scapula up to the site of insertion on the humerus. Variant morphology along with unusual pattern and site of insertion of teres minor muscle was noted in two (3.33%) cadaveric specimens. The results of the present study highlight the continuous phylogenetic change taking place in a RCM. Familiarity about the variation reported is paramount for the surgeons planning rotator cuff surgery and other invasive procedures in shoulder region. The current data will be significant for radiologist interpreting magnetic resonance imaging scans to report post-operative outcome of rotator cuff surgeries.